Pelatihan Penggunaan Sosial Media bagi Pelaku Seni Langgam Makassar - Ambarwati, Nilam; Syasbila, Adinda Futri; Yudistira, Muh. Isra; Syamsuar; Poerwanto, Bobby (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
This community service activity aims to train Makassari Langgam music artists in Taeng Village to be able to help them in editing videos, flyers, and promoting their works where previously one of the problems in Taeng Village was the reduction in cultural events that they could fill and they were also less recognized. To solve this problem, the team held a discussion with the village head and agreed to conduct video editing and social media training so that they could learn to edit videos and promote their work. The participants in this activity numbered 51 people consisting of groups of young and old artists. In addition to the resource persons providing material, there were also teams that accompanied participants in creating accounts, editing videos and posting works on group accounts and their respective accounts. Before they joined this program, they only used social media as a platform to exchange news, see information from celebrities and Indonesian news. Currently, they use social media not only for that because they can edit videos and make social media a platform that helps them brand their Langgam Group and can promote their work.